Analysis of farm performance to realize the sustainability of organic cabbage vegetable farming in Getasan Semarang, Indonesia - Winahyu Wulansari; Rahayu Endang Siti; Darwanto Dwidjono Hadi; Harisudin Mohamad (Open Agriculture)
Increasing farmers’ income is possible through high-value markets. Employment, access to financing, and technical support have favorable effects and a rise in income. This research seeks to establish the sustainability of organic cabbage farming through economic performance analysis. Quantitative research methods were conducted in this research. Descriptive quantitative analysis was performed with PLS-SEM software. The research data comprise primary data and secondary data. Of the 11 pathway coefficients in this study, only 9 were significant. The protection variable was positively related to the production optimization construct but did not significantly affect financial performance. The variable “healthy and safe” was positively associated with significant constructs of “financial performance” and “production optimization.” The variable “capacity development” was positively related to the constructs of “financial performance” and “production optimization.” The “technical” variable was significantly positively associated with the construct of “financial performance” but did not significantly affect the construct of “optimization of production.” The variable “production optimization” is positively related to the construct of “financial performance” and the construct of “farm performance” of farmers. Agricultural extension and training must be carried out to improve farmers’ technical knowledge. Government subsidies to support organic farming are also needed to ensure the sustainability of organic cabbage farming in the Semarang district.